Knowledge, usage and perceptions of selected UP Diliman students from College of Human Kinetics on dietary supplements - Castillo, Valerie Anne E.; Gonzaga, Vanessa Joyce V.; Patigdas, Rojenn Claire G.
Dietary supplements (DS) are popular among college students to help counterbalance harmful behaviors and enhance general health. However, they are generally unaware of health claims, and product safety. Given that such items are potentially harmful, there is a need to explore their DS use. Hence, this mixed-methods descriptive research aimed to describe the knowledge, usage, and perceptions of selected UP Diliman students from the College of Human Kinetics on DS. Thirty-three participants between 18 to 24 years old were recruited through snowball sampling. Results show that students are well-informed about the safety and regulation of DS but demonstrate a low level of knowledge on dosage, specifically on Vitamin C, DS in sports, and managing chronic diseases. In addition, their top reasons for using DS are boosting the immune system, increasing muscle mass, improving bone strength, and preventing diseases which makes vitamins, multivitamins, and protein supplements the most consumed DS. Furthermore, the majority of participants perceive that dietary supplements are effective based on evidence and experience in the improvement of overall health and performance. However, they still have limitations and should only be used secondary to natural food sources. The findings of this study will help school, community leaders, nutritionists and allied medical professionals strengthen nutrition education through social media, community and school activities. For future studies, researchers may look into the correlation between DS knowledge and usage among students in other universities and colleges.